CIRCUMCISION IN MOZAMBIQUE, DIALOGUE BETWEEN TRADITIONS, BIOETHICS AND BIOMEDICINE - Mabutana, Carlos (Seven Editora, 2025)
This paper is part of a qualitative research, based on an ethnographic study, carried out with the Makonde ethnic group, in southern Mozambique. It reflects on the traditional practice of circumcision as an initiation ritual among the Makonde and the influence it suffered in contact with other ethnic groups and religions and with the biomedicine paradigm. It develops a brief historical characterization of circumcision in the cultural traditions of different ethnic groups in the country and points out challenges of the practice of traditional circumcision in dialogue with biomedical interventions related to HIV prevention. It highlights the role of health workers, bioethicists, and anthropologists in the understanding of singular stories of native ethnic groups and their forms of resistance or adherence to epistemologies from contemporary scientific medicine. Also argues the need to address informed consent and human rights of young males who participate in this type of intervention.DOI: https://doi.org/10.56238/sevened2025.036-130